Role Agricultural Sector in Restoring the Growth of National Economy (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article investigated the development of the agricultural sector of Ukraine in the last five years, defined its role in the stabilization of the national economy. It is proved the inefficiency of the present of the state of agricultural policy, disclosed that agriculture is an important sector of the economy, off the functioning of which depends the development of the country, proposed by directions comprehensive solution of problems of stable development of rural areas with the priority of social objectives, identified challenges that need to be addressed to increase the contribution of the agrarian sector in the overall economic growth of the national economy. Grounded the necessity to increase the prestige of work in rural areas, to provide state support for agricultural production and to introduce differentiated tax system and to introduce differentiated tax system which would take into account the ratio of landowners and tenants to the preservation of the fertility of the land resources that they use.
Keywords: land, agrarian complex, national economy, economic growth, clusters, tax system